Human Skeletal Muscle Mitochondria Responses to Weight Loss Induced by Bariatric Surgery or Lifestyle Intervention - van der Kolk, Birgitta W.; Heinonen, Sini; White, James W.; Wagner, Anita; Karppinen, Jari E.; Saari, Sina; Muniandy, Maheswary; Metsikkö, Simo; Dillon, Eugène T.; Groop, Per‐Henrik; Saarinen, Tuure; Le Roux, Carel W.; et al. (Wiley, 2026)
Aim
We investigated how weight loss induced by bariatric surgery or lifestyle intervention affects skeletal muscle mitochondrial metabolism.
Methods
We studied two weight-loss cohorts: RYSA (BMI ≥ 35 kg/m2; n = 39, including 18 with diabetes) undergoing bariatric surgery, and CRYO (BMI ≥ 30 kg/m2; n = 19) undergoing a lifestyle intervention with a low-calorie diet. Assessments were performed at 5–6 and 12 months and included muscle proteome (LC–MS/MS), mitochondrial biogenesis by mtDNA amount (qPCR), number and morphology (transmission electron microscopy) in both cohorts, and mitochondrial oxidative capacity (high-resolution respirometry) in the surgery cohort.
Results
Both cohorts achieved clinically meaningful weight loss, greater following surgery (24.4% vs 9.0% at 12 months). Per 1% weight loss, bariatric surgery was associated with significant downregulation of glycolysis pathways at 12 months. OXPHOS complex subunit proteins were associated with upregulation in individuals without diabetes but downregulation in those with diabetes. Lifestyle intervention was associated with downregulated OXPHOS complex subunits at 5 months. Mitochondrial morphology remained unchanged, while mtDNA amount correlated negatively with weight loss percentage in both cohorts. In the surgery cohort, complex I and complex I + II-mediated respiration increased 3.2- and 2.9-fold at 12 months, reflecting improved oxidative capacity.
Conclusion
Bariatric surgery was associated with increased skeletal muscle mitochondrial respiration despite unchanged morphology and reduced mtDNA amount, whereas lifestyle-induced weight loss showed a transient downregulation of OXPHOS-related proteins with other mitochondrial markers remaining stable. Surgery-induced weight loss may reflect improved mitochondrial efficiency in skeletal muscle, potentially influenced by diabetes status. Long-term functional mitochondrial adaptations after weight loss require future studies.